До питання про вихідні принципи археології - Захарук, Ю.М. (Археологія, 1997)
Оскільки вихідним об’єктом археологічного пізнання є археологічні пам'ятки, то саме теорія археологічного джерелознавства може претендувати на роль фундаментальної. Статья посвящена разбору взглядов В. Ф. Генинга на проблему исходных принципов археологического познания, сформулированных в монографии «Структура археологического познания». Исходя из философского определения объекта науки, а также познавательного процесса в археологии объектом познания здесь выступает не общество прошлого, как считал В. Ф. Генинг, а археологические источники. Общества прошлого составляют цель, конечным результат познания в археологии.
Неправомерным представляется и определение в качестве предмета исследования в археологии установление закономерностей социально-исторического развития отдельных обществ древности. Столь расширенное понимание целей археологии приводит к включению в собственно археологическое познание общесоциологического и исторического уровней и к игнорированию роли источниковедения. Поскольку исходным объектом археологического познания выступают археологические памятники, то именно теория археологического источниковедения может претендовать на роль фундаментальной. The paper is devoted to the analysis of V. F. Gening’s views on the problem of starting principles in the archaeological knowledge formulated by him in the monograph «The Structure of Archaeological Knowledge» (Kyiv, 1989). Proceeding from the philosophical determination of the object of science, as well as from the cognitive process in archaeology, the object of knowledge in archaeology is not a society of the past, as V. F. Gening believed, but archaeological sources. Societies of the past are the aim and the final result of knowledge in archaeology.
It is also erroneously to represent determination of regularities in the socio-historical development of certain ancient societies as a subject of the study in archaeology. The so expanded comprehension of objectives in archaeology leads to incorporation of general sociological and historical levels to the archaeological knowledge proper and to neglection of the source study. As archaeological relics are the starting objects of the archaeological knowledge, it is the theory of archaeological source study that may have a claim on the role of the fundamental theory.